Associations between urinary concentrations of bisphenols and serum concentrations of sex hormones among US. Males - Chichen Zhang; Yuehong Luo; Shi Qiu; Xinyi Huang; Kun Jin; Jiakun Li; Mi Yang; Dan Hu; Xiaonan Zheng; Zhongyuan Jiang; Mingda Wang; Xiaoli Zou; et al. (Environmental Health, 2022)
Abstract Background Bisphenol A (BPA) exposure and its structural analogs (BPS and BPF) might cause endocrine alterations and adverse physiological effects. Few studies to date have directly explored the association between its structural analogs (BPS, BPF) and sex hormones in adult male participants. Therefore, we aimed to assess the associations between BPA, BPS, BPF, and sex hormones in American adult men. Methods We used data from the U.S. National Health and Nutrition Examination Survey 2011–2016. We excluded participants without data available on sex hormones and urinary bisphenols. Furthermore, participants consuming sex hormone medications were excluded. Multivariable regression models were performed to assess the association between bisphenols and sex hormones. Results In this study, 2367 participants were included. Of 2367, in 1575 participants, the data on BPS and BPF were available. We found that a per unit increase in BPF was associated with 0.575 ng/dL higher total testosterone (TT) (Model 2: 95% CI: 0.047, 1.103, P = 0.033). However, there was no significant association between BPA or BPS and TT. Furthermore, increased BPA and BPS levels were associated with higher levels of sex hormone-binding globulin (SHBG) (Model 2: β = 0.364, 95% CI: 0.158, 0.571; β = 0.25, 95% CI: 0.071, 0.429, respectively). Additionally, participants in the highest BPA exposure quartile (quartile 4) had 4.072 nmol/L higher levels of SHBG than those in quartile 1 (Model 2: 95% CI: 0.746, 7.397, P = 0.017; P for trend =0.005). Both BPA and BPS were negatively associated with free testosterone (FT, nmol/L) after full adjustment (Model 2, β = − 0.01%, P = 0.0211, P = 0.0211; Model 2, β = − 0.01%, P = 0.0258, respectively). However, BPF was positively associated with FT (Model 2, β = 0.0029%, P = 0.0028). Conclusion Our study indicated that exposure to both BPA and its substitutions could alter sex hormone levels. This finding supports the possibility that human exposure to bisphenols at environmental levels might affect the endogenous hormone balance.